DAMPAK SUHU PENYIMPANAN TERHADAP MUTU BIOFISIK DAN ORGANOLEPTIK PASCAPANEN KOMODITAS HOLTIKULTURA - Widia Pangestika; Rifatul Masrikhiyah; Eka Wijayanti (Program Studi Ilmu Teknologi Pangan Universitas Muhadi Setiabudi, 2026)
Quality degradation in fresh horticultural products macroscopically manifests in color changes and visual appearance, serving as primary determinants for consumer acceptance. This qualitative descriptive study aimed to map the visual deterioration patterns of ten selected commodities (apple, banana, tomato, cucumber, carrot, red bell pepper, orange, oyster mushroom, onion, and broccoli) over three days of storage. The thermal treatments evaluated included room temperature (28°C), refrigeration (4°C), and freezing (-18°C). Observations were objectified using a structured rubric encompassing chromatic fluctuation, epidermal integrity, dehydration percentage, and tissue exudation. Thematic analysis revealed that refrigeration generally decelerated the senescence rate but specifically triggered chilling injury pathogenesis, such as asymmetrical discoloration in tropical commodities like bananas. Conversely, freezing effectively preserved initial pigment stability, yet ice crystal induction caused mechanical damage resulting in severe drip loss post-thawing, particularly in high-moisture matrices. Meanwhile, ambient temperature accelerated osmotic dehydration and extreme enzymatic browning, with the most massive deterioration observed in oyster mushrooms. Based on these findings, it is concluded that visual indicator observations grounded in thermal biophysical mechanisms are highly applicable as a practical quality control instrument in food industry management systems